(Invited) Electrochemical Sensing Using Molecule-like Gold Nanoclusters. (16th August 2016) - Kumar, S. Senthil; Kwak, Kyuju; Lee, Dongil
Abstract : Quantum-sized gold nanoclusters of size <2 nm possess unique and size-dependent redox behavior. Au25 nanoclusters (Au25 NCs), in particular exhibit redox potentials closer to conventionally used mediators such as ferrocyanide and ferrocene and hence our objective was to utilize these clusters as mediators in the development of electrochemical sensors and biosensors. We have prepared modified electrodes containing Au25 NCs and tested their electrocatalytic activity and amperometric sensing behavior. Au25 NCs have behaved as an electronic conductor and redox mediator as well. Further, we have tuned the electrostatic charge on these clusters by using glutathione ligand and improved the selectivity of the modified electrode towards charged analytes. Finally, in order to examine the utility of the Au25 NCs in electrochemical biosensing, an ionic liquid containing Au25 NC has been prepared (Au25 IL). The composite of Au25 IL and glucose oxidase enzyme has exhibited to be an excellent biosensor towards the determination of glucose.